Comparison of Crop Yield Estimates Obtained from an Historic Expert System to the Physical Characteristics of the Soil Components—A Project Report - Edward B. Rayburn; Tom Basden (Agronomy, 2022)
Crop yields vary due to soil type. Expected crop yields are reported in published soil surveys based on the knowledge of local conservation and extension professionals. Crop yields have increased over the years due to improved genetics and management. The objective of this project was to compare historic expected crop yields to soil physical characteristics and to update expected yields for West Virginia soils in the United States National Soils Information System (NASIS). Regression analysis found that soil physical characteristics explained 57 to 65% of the variation in corn and hay yields. Corn and hay yield regressions calculated from a regression data set predicted yields for crops on soils in a test data set without bias and with residual errors of 10 to 15%. Updated crop yields under good management on more productive soils were obtained by surveying farmers and variety trials conducted in West Virginia and surrounding states. The updated yields and relative historic yields were used proportionally to update expected crop yields by soil series. The updated yields were reviewed by local conservation professionals and adjusted as needed based on local experience. These updated yields are now being used as the expected crop yield for the West Virginia soil series in the NASIS.